Replication Data for: Modulation of Polar Mesospheric Summer Echoes (PMSE) with HF Heating during low solar illumination - Gunnarsdottir, Tinna Lif; Poggenpohl, Arne; Mann, Ingrid; Mahmoudian, Alireza; Dalin, Peter; Haeggstroem, Ingemar; Rietveld, Mike (DataverseNO, 2022)
Reproduction data for heating of Polar Mesospheric Summer Echoes measured with EISCAT VHF radar. Included in this dataset are all figures related to the paper in pdf format and good quality (at least 300 PDI). The code to reproduce these figures is given in code_plots. This code takes radar data as input and the output is; PMSE with heating; overview, scatter, and histograms. The code includes a main function/script and several support functions. Additionally, a short code to calculate the photon flux for a given time of year and day is included along with text files necessary to reproduce the associated figure from the paper.